Evaluation of Organic-Mineral Fertilizer Components: A Multi-Criteria Analysis Based on Various Factors - Muthumari G (International Journal of Trends in Horticulture, 2025)
This study explores the potential of organic-mineral fertilizers as sustainable alternatives to synthetic options, evaluating ten such fertilizers, including coffee grounds, poultry eggshells, bone meal, Fish Emulsion, compost, cow manure, wood ash, biochar, seaweed extract, and green manure. A multi-criteria analysis assessed factors like effectiveness, cost, environmental impact, availability, and waste potential. Coffee grounds and poultry eggshells performed best due to their high nutrient content and positive soil effects, with coffee grounds excelling in moisture retention and poultry eggshells improving soil pH. Other fertilizers like compost and cow manure showed sustainability benefits, while bone meal and Fish Emulsion were less favorable due to higher costs and environmental concerns. The study emphasizes the value of waste-derived fertilizers in reducing reliance on synthetic products and improving soil health. Recommendations include further research into production methods, long-term field trials, and the development of waste-based fertilizer technologies for more sustainable agricultural practices.
Keywords: Agriculture; Environmental impact; Fertilizer; Soil fertility; Soil health improvement; sustainable